Optimization of physical characterization, skin permeation of naproxen from glycofurol-based topical gel - Barakat, Nahla S (Asian Journal of Pharmaceutics (AJP), 2014)
In view of good skin tolerability, glycofurol was used as a vehicle-based gel and its effect on the topical penetration of Naproxen (NAP) was investigated. The aim of this study was to develop a suitable gel with bioadhesive property, spreadability, and viscosity for a topical anti-inflammatory effect.Three gelling agents were examined: Carbopol 974P, GantrezÂ  AN 119, and Polyvinylpyrroloidone PVP K30. Skin permeation rates and lag times of NAP were evaluated using the Franz- type diffusion cell, in order to optimize gel formulation. The permeation rate of the NAP-based gel across excised rat skin was investigated. A significant increase in permeability parameters such as steady-state flux (Jss), permeability coefficient (Kp), and penetration index (PI) were observed in the optimized formulation containing 2% Transcutol as a permeation enhancer. From the skin irritation test, it was concluded that the optimized novel tetraglycol-based gel formulation was safe to be used for transdermal drug delivery. The developed naproxen / glycofurol-based gel appeared promising for dermal and transdermal delivery of naproxen and could be applicable with water-insoluble drugs, which would circumvent most of the problems associated with drug therapy.